Kesan Latihan Kemahiran Sosial Terhadap Konsep Kendiri Pelajar - Amin Johari, Ghazali (1995)
This study is to observe the effects of social skills training on the pupils self-concepts. Thirty pupils from four different schools in Ipoh namely Sekolah Menengah Megat Khas, Sekolah Menengah Hulu Kinta, Sekolah Menengah Kampung Pasir Puteh and Sekolah Menengah Gunung Rapat, were taken as subjects of the study. The module used was the communicational skills module. The activities in the module involving the variables of family self, personal-emotional self, physical self, social-behavioral self and satisfaction-moral ethical self. The Martinek-Zaichkowsky Self -Concept Scale for Children was used for the pre and the post-test. T-test was used for the data analysis. The result shows that there are some improvement in the selfconcept of the experimental groups. There is no significant difference between the boys and the girls except for the physical self where the boys show a better performance.